Profitable horizontal mergers: A market structure-oriented view - Steffen Huck; Kai A. Konrad; Wieland Müller (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2000)
We propose a model in which mergers exert a more pronounced effect on the structure of a market than simply reducing the number of competitors. We show that this may render horizontal mergers profitable and welfare-improving even if costs are linear. The results help to reconcile theory with various empirical findings on mergers.
urn:nbn:de:kobv:11-10047335
Keywords: 330; efficient hedging; quantile hedging; jump-diffusion; martingale measure.